Examining the key factors affecting e-service quality of small online apparel businesses in Malaysia - Noorshella Che Nawi; Abdullah Al- Mamun; Nursalihah Ahmad Raston (2015)
E-service quality (eSQ) is increasingly recognized as an important aspect, as well as the key to determining the competitive advantage and factor in the long-term retention of firms operating online. This study, therefore, is aimed at identifying the key determinants of eSQ among the small online apparel businesses in Malaysia. This study used a cross-sectional design, and data were collected from 765 customers who purchased apparel online at the point-of-purchase. Findings of this study indicate that “product information quality,” “website design,” “security and privacy,” and “expected consumer service” are the key determinants of eSQ among small online apparel businesses in Malaysia. The implication for the owner-managers of the apparel businesses in Malaysia is that they must be aware of the significance of the key eSQ indicators while designing their businesses, to attract and retain customers.